Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Need help with the First Fundamental Theorem of Calculus?

I’m having a problem with an equation used in the First Fundamental Theorem of Calculus. I’ve found it in a textbook (author from MIT), on Wikipedia and on several web sites.

F is antiderivative

f is function

F(x) = (integral) (from a to x) f(t) dt

My first thought when I saw this was that it would only be true if a=0. I decided to test it with a simple function f(t) = 2t, a simple range [a,b] = [1,5] and setting the point of interest, x, to be equal to 3 (x=3).

f(t) = 2t

F(x) = t^2

x = 3

F(3) = 9

(integral) (from 1 to 3) 2t dt = t^2 | (from 1 to 3) = 9 - 1 = 8

9 does not equal 8.

Is there a flaw in my logic? (showing me where I went wrong would constitute an answer)

Has this problem been previously acknowledged? (showing an internet reference to this problem would also constitute an answer)

Update:

(integral) (from a to x) f(t) dt <-- this is a definite integral

For the First Fundamental Theorem of Calculus, we have the closed interval [a,b] and x is a point on the interval.

There is nothing stated in the theorem to indicate that I was supposed to set a=0.

Update 2:

The question has been answered - F(x) must include a constant C. For this equation, C will be determined by the value of a.

3 Answers

Relevance
  • David
    Lv 7
    1 decade ago

    an anti-derivative is a function, not a number.

    suppose we define a function by:

    F(x) = ∫[a,x] 2t dt

    then F(x) is NOT t^2 (first of all, t is a parameter, not the variable of the function. the variable is x).

    a little thought should convince you that

    F(a) = ∫[a,a] 2t dt = 0 (an integral over 0 distance is 0).

    so in your example, where you chose a = 1, that means:

    F(1) = 0. now clearly, F(x) = x^2 does not satisfy F(1) = 0.

    what you are missing is that:

    F(x) should be x^2 - 1.

    x^2 and x^2 -1 are both anti-derivatives of 2x.

    anti-derivatives are not unique, if F(x) is an anti-derivative of f(x),

    so is F(x) + C, where C can be any constant (number).

    it is indeed true that F(x) = x^2 -1 satisifies F(3) = 8.

    more generally, if F(x) is an anti-derivative of f(x),

    then ∫[a,x] f(t) dt = F(x) - F(a) (note the second term !!!!).

    now F(x) = x^2 -1 and G(x) = x^2 are both anti-derivatives, let's compute

    G(3) - G(1) and F(3) - F(1):

    G(3) - G(1) = (3)^2 - (1)^2 = 9 - 1 = 8.

    F(3) - F(1) = (3^2 - 1) - (1^2 - 1) = 8 - 0 = 8.

    now, for simple powers:

    ∫[0,x] t^n dt = x^(n+1)/(n+1) - 0 = x^(n+1)/(n+1)

    whereas

    ∫[a,x] t^n dt = x^(n+1)/(n+1) - a^(n+1)/(n+1)

    note that the starting point of the integral, a, works

    as an adjustment factor, to "pin down" the constant term of the anti-derivative.

    this is why ∫[a,x] f(t) dt is called a DEFINITE integral.

    ∫ f(t) dt, on the other hand, is "indefinite", and one has to write the anit-derivative as:

    F(x) + C. <---don't forget the C (sometimes we don't know what "C" is!).

  • 1 decade ago

    You made a common mistake

    Since F(x) is antiderivative of f(x) and f(x) = 2x, then

    F(x) = x^2 + C (and not x^2)

    Using f(t) = 2t, and a = 1, we get:

    F(x) = ∫[from 1 to x] f(t) dt

    F(x) = ∫[from 1 to x] 2t dt

    F(x) = t^2 |[from 1 to x]

    F(x) = x^2 - 1

    Now we get:

    F(3) = 3^2 - 1 = 8 (which does match your result ∫₁³ 2t dt = 8)

    and F'(x) = 2x = f(x)

    ====================

    Please note that

    ∫[from a to x] f(t) dt and ∫[from b to x] f(t) dt will give different results for a ≠ b

    These results will differ ONLY in the constant. Therefore, both will give valid antiderivatives of f

  • 5 years ago

    If F(a,x) = integr60f42a513a57ecc111d234a1a775ad5te[60f42a513a57ecc111d234a1a775ad560f42a513a57ecc111d234a1a775ad560f42a513a57ecc111d234a1a775ad5] f(t) dt60f42a513a57ecc111d234a1a775ad5 then F'(a,x) = f(a,x) yet yours is t60f42a513a57ecc111d234a1a775ad5n60f42a513a57ecc111d234a1a775ad5 inste60f42a513a57ecc111d234a1a775ad5d of 60f42a513a57ecc111d234a1a775ad560f42a513a57ecc111d234a1a775ad5 so that you should 60f42a513a57ecc111d234a1a775ad5pply the ch60f42a513a57ecc111d234a1a775ad5in rule 60f42a513a57ecc111d234a1a775ad5fter utilizing the concept. the following is going: Y' = root(6t60f42a513a57ecc111d234a1a775ad5n60f42a513a57ecc111d234a1a775ad5 + root(t60f42a513a57ecc111d234a1a775ad5n60f42a513a57ecc111d234a1a775ad5)) * sec^2 a,x

Still have questions? Get your answers by asking now.